Assessing the impact of regional transformative outreach activities aimed at widening university access, and participation among under-represented groups in schools. (28th February 2023) - Rose, Anthea; Mallinson, Lucy
Transformative outreach activities, including study skills workshops, motivational speakers and campus visits, are common across the educational sector. However, little is known about their impact on non- traditional students' decisions regarding higher education. Designed to raise the higher education aspirations of young people in Years 9 to 13 (aged 13 – 18), the Uni Connect programme delivers outreach activities to young people in areas in England, UK, where higher education participation is much lower than expected based on attainment in national examinations taken at ages 15 and 16. This article presents the findings of a student activity survey conducted as part of the Lincolnshire Uni Connect regional evaluation. Surveys were sent to participating students between May and July 2020 to assess the impact of the outreach activities they had received during the school year. A total of 672 valid responses were received: 247 (37%) from Uni Connect students. Impact was measured against the NERUPI evaluation framework, which comprises five elements: knowing, choosing, becoming, practicing and understanding, and is designed to determine the success of widening participation initiatives. The data showed activities focusing on NERUPI outcomes 'know' and 'become' were the most effective. Findings from the study raise important questions about the choice and effectiveness of transformative activities aimed at underrepresented groups.